Natural Killer Cells Offer Differential Protection From Leukemia in Chinese Southern Han - Deng, Zhihui; Zhao, Jun; Cai, Siqi; Qi, Ying; Yu, Qiong; Martin, Maureen P.; Gao, Xiaojiang; Chen, Rui; Zhuo, Jiacai; Zhen, Jianxin; Zhang, Mingjie; Zhang, Guobin; et al. (Frontiers in Immunology, 2019)
Interactions of human natural killer (NK) cell inhibitory receptors with polymorphic HLA-A, -B and -C molecules educate NK cells for immune surveillance against tumor cells. The KIR A haplotype encodes a distinctive set of HLA-specific NK cell inhibiting receptors having strong influence on immunity. We observed higher frequency of KIR A homozygosity among 745 healthy Chinese Southern Han than 836 adult patients representing three types of leukemia: ALL (OR = 0.68, 95% CI = 0.52–0.89, p = 0.004), AML (OR = 0.76, 95% CI = 0.59–0.98, p = 0.034), and CML (OR = 0.72 95% CI = 0.51–1.0, ns). We observed the same trend for NHL (OR = 0.47 95% CI = 0.26–0.88 p = 0.017). For ALL, the protective effect of the KIR AA genotype was greater in the presence of KIR ligands C1 (Pc = 0.01) and Bw4 (Pc = 0.001), which are tightly linked in East Asians. By contrast, the C2 ligand strengthened protection from CML (Pc = 0.004). NK cells isolated from KIR AA individuals were significantly more cytotoxic toward leukemic cells than those from other KIR genotypes (p < 0.0001). These data suggest KIR allotypes encoded by East Asian KIR A haplotypes are strongly inhibitory, arming NK cells to respond to leukemogenic cells having altered HLA expression. Thus, the study of populations with distinct KIR and HLA distributions enlightens understanding of immune mechanisms that significantly impact leukemia pathogenesis.